Can carbon based import tariffs effectively reduce carbon emissions? - Michael Hübler (Kiel Institute for the World Economy (IfW), 2009)
We estimate CO2 implicitly contained in traded commodities based on the GTAP 7 data: While net carbon imports into the industrialized countries amount to 15% of their total emissions, net carbon exports of the developing countries amount to 12% of their total emissions, and net carbon exports of China amount to 24% of China's total emissions. We also analyze policies under a global per capita emissions based contraction and convergence regime with emission trading: When China joins the regime, the developing countries will benefit, while the industrialized countries will be almost unaffected. When China does not join the regime and instead a carbon content based border tax is imposed, the industrialized countries will significantly benefit, while China will be significantly worse off. The effect of the border tax adjustment on the global carbon price and on global emissions seems negligible.
Keywords: F13; F18; Q54; 330; Carbon content of trade; border tax adjustment; climate policy; contraction and convergence; China; Klimaschutz; Kohlendioxid; Außenhandel; Einfuhrumsatzsteuer; Ökosteuer; Internationale Wirtschaftsbeziehungen; Emissionshandel; Wirkungsanalyse; Industriestaaten; Entwicklungsländer; China